Pengaruh Edukasi Booklet Hiv Terhadap Peningkatan Pengetahuan Dan Sikap Remaja Di SMA TPI Basilam Kecamatan Wampu Kabupaten Langkat Tahun 2022 - Nasution, Naimah; Insani, Septa Dwi; Natali, Kristin (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
HIV stands for human immunodeficiency virus, which is a virus that attacks the human immune system. People who are HIV positive or have HIV The World Health Organization (WHO) states that HIV/AIDS is still a global health problem and is recorded as the cause of death for 32 million people in the world. HIV/AIDS is one of the most devastating and very serious multinational problems. Education is a learning process that is carried out both formally and non-formally which aims to educate, provide knowledge and develop the potential that exists in every human being, then realize the learning process better. to a particular stimulus or object. Which already involves the relevant emotional opinion factor (happy-not happy, unhappy, agree-disagree, good-bad, etc.) Adolescents start from the developmental phase of rapid growth and development, accompanied by sexual maturation and social pressure, Quasi Experiment design. With the method of one group pre-post test design. The test used in this study is the Wilcoxon test with the result of sig 0.000 which shows that the results have an effect on the increase in knowledge and attitudes of adolescents at Tpi Basilam High School, Wampu District, District Keywords: HIV, Education, Attitude